Japanese Marxist: A Portrait of Kawakami Hajime, 1879-1946 - Schonberger, Howard (Labour / Le Travail, 1980)
This article reviews the book, "Japanese Marxist: A Portrait of Kawakami Hajime, 1879-1946," by Gail Lee Bernstein.